(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article provides a scientific analysis of the development and characteristics of competition in the higher education services market of the Republic of Uzbekistan. It examines the interaction between public and private sectors in higher education, the role of quality indicators, pricing mechanisms, marketing strategies, and the implementation of innovative approaches as key factors influencing competitive dynamics. The article also explores internal and external forms of competition among higher education institutions, mechanisms to enhance competitiveness, and the regulatory influence of the state on market equilibrium. Based on statistical data, legal frameworks, and international experience, the current state and future prospects of Uzbekistan’s higher education services market are evaluated.